Gut Microbiota, the Ketogenic Diet and Epilepsy - Egidio Spinelli; Robyn Blackford (Pediatric Neurology Briefs Publishers, 2018)
Investigators from the Children's Hospital of Fudan University assessed changes in the gut microbiome of pediatric patients with intractable non-lesional epilepsy between responders and non-responders to the ketogenic diet.